Clinical Biochemical Significance of STAT6, ERG, and miR-647 Expression in Prostate Cancer: Associations With Tumor Aggressiveness and Patient Prognosis: STAT6, ERG, and miR-647 in Prostate Cancer - Hong, Xin; Zhao, Lin; Wang, Tian; Yang, Xiaobing; Hao, Changzhen (Journal of Medical Biochemistry, 2026)
Background: Reliable molecular indicators that can facilitate early detection and prognosis prediction in prostate cancer are still insufficient. Although Transcription 6 (STAT6), ERG, and microRNA-647 (miR-647) have recently been recognized as key participants in tumor-related signaling pathways, their specific biochemical functions in the context of prostate cancer have yet to be clearly defined. This study evaluated the expression profiles of STAT6 mRNA, ERG mRNA, and miR-647 in prostate cancer tissue and explored their associations with clinicopathological features and patient outcomes. Methods: Surgical specimens were obtained from 70 patients, including both prostate cancer tissues and their corresponding adjacent non-tumorous counterparts. Quantitative real-time PCR (qPCR) was used to measure STAT6 mRNA, ERG mRNA, and miR-647 expression. The relationships between biomarker expression and clinical parameters—including age, tumor diameter, lymph node involvement, T stage, and pathological differentiation—were examined. Overall survival (OS) and progression-free survival (PFS) were evaluated using Kaplan–Meier curves with log-rank comparisons, while Spearman correlation analysis was employed to determine the associations among the examined molecular markers. Results: Levels of STAT6 mRNA, ERG mRNA, and miR-647 were markedly higher in prostate cancer specimens than in the paired non-tumorous tissues (P<0.05). Elevated expression of these molecules corresponded to the presence of lymph node metastasis, higher T stage, and unfavorable histological differentiation, whereas no significant associations were observed with patient age or tumor dimensions. Patients with high STAT6, ERG, or miR-647 expression exhibited significantly reduced OS and PFS compared with low-expression groups (all P<0.05). miR-647 expression positively correlated with STAT6 mRNA (r=0.867) and ERG mRNA (r=0.724) (P<0.05). Conclusion: STAT6, ERG, and miR-647 exhibit pronounced overexpression in prostate cancer, and their elevated levels are closely linked to more aggressive tumor behavior and unfavorable clinical outcomes. Their coordinated dysregulation suggests a potential molecular axis involved in prostate cancer progression. These molecular indicators have the potential to enhance biochemical risk stratification and support more refined molecular assessments in routine clinical settings.